Lipoma Tongue – A Rare Site For A Common Neoplasm - Ranjan Agrawal (National Journal of Laboratory Medicine, 2012)
Lipomas are among the most common mesenchymal neoplasms, however, only 15%-20% involve the head and neck and 1%-4% affect the oral cavity. Lipoma of the tongue represents about 0.3% of all benign lesions of the oral cavity. A 12-year-old boy presented with a globular swelling over the middle of dorsum of tongue since last 4 months duration. The swelling was apparently non-progressive. It was excised under local anaesthesia and histopathologically diagnosed as lipoma tongue. The case is being presented due to its rarity.